The European Consultation-Liaison Workgroup (ECLW) Collaborative Study. I. General outline. - Huyse, F (2012)
Previous C-L psychiatric service research is seriously limited by its parochial nature; very few results can be generalized outside of the hospital in which the original study was performed because of differences in the nature of the hospital and the type of C-L service. This article presents the general outline and methodology of a European multicentered C-L service delivery study effected by the European Consultation-Liaison Workgroup for General Hospital Psychiatry and Psychosomatics (ECLW). The study is unique in its kind as it allows the comparison of very different C-L services; for example, some services are run by C-L psychiatrists, others are run by C-L psychosomaticists and the study encompasses a large variety of different settings. As a result, both common factors in C-L service delivery and specific local patterns can be explored. The overall hypothesis tested in this study was that the most developed services would see (as well as more patients) a wider variety of clinical problems than small services. The implication is that the absence of well-developed C-L services in a general hospital may mean that there are patients with unmet mental health needs. In separate articles the training and reliability testing of the new Patient Registration Form (PRF) and the Institutional and Provider characteristics will be described. The former includes the use of ICD-10 in the general hospital setting. This study is a collaborative effort made by 226 consultants from 56 psychiatric C-L services in 11 countries. Each consultant recorded details of 1 year's caseload leading to a thorough description of 14,717 patients collected between 1991 and 1993. The advanced methodology included a multicentered international approach, rigid training for all participating consultants, and the development and testing of new instruments. This will allow us to assess the impact of important structural and process variables on the outcome of C-L service delivery in several European countries. These results will be reported in papers both in the international and national literature of the participating countries.